2001
DOI: 10.4049/jimmunol.167.11.6545
|View full text |Cite
|
Sign up to set email alerts
|

Fc Receptor-Mediated Immunity Against Bordetella pertussis

Abstract: The relevance of specific Abs for the induction of cellular effector functions against Bordetella pertussis was studied. IgG-opsonized B. pertussis was efficiently phagocytosed by human polymorphonuclear leukocytes (PMN). This process was mediated by the PMN IgG receptors, FcγRIIa (CD32) and FcγRIIIb (CD16), working synergistically. Furthermore, these FcγR triggered efficient PMN respiratory burst activity and mediated transfer of B. pertussis to lysosomal compartments, ultimately resulting in reduced bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 52 publications
4
56
1
5
Order By: Relevance
“…However, results from previous studies using similar OPA protocols and PMNs as effector cells indicate that the internalized B. pertussis bacteria are readily killed in this process (23,25,33). In addition to OPA, the direct complement killing of the bacteria also may play a role.…”
Section: Discussionmentioning
confidence: 62%
“…However, results from previous studies using similar OPA protocols and PMNs as effector cells indicate that the internalized B. pertussis bacteria are readily killed in this process (23,25,33). In addition to OPA, the direct complement killing of the bacteria also may play a role.…”
Section: Discussionmentioning
confidence: 62%
“…We have only observed efficient phagocytosis of B. pertussis by (29), by mutagenesis (32), or by neutralizing antibodies (22,31). In contrast, one study reported efficient phagocytosis of antibodyopsonized B. pertussis (26). In this study, phagocytosis was monitored by a flow cytometry assay that involved incubation at 4°C to allow bacterial attachment followed by a shift to 37°C to permit phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…A common technique to uncouple the process of attachment from internalization involves incubating the cells at low temperatures, which prevents internalization but not attachment, followed by a shift to 37°C, which restores conditions permissive for internalization. In one study (26), efficient phagocytosis of B. pertussis was reported for an assay that uncoupled attachment and phagocytosis by using a temperature shift. However, the expression of CR3 (Fig.…”
Section: Cr3 Receptor Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoglobulin G (IgG) fractions from pooled sera of pertussis patients with high anti-B. pertussis antibody titers, as measured by enzyme-linked immunosorbent assay (27), were isolated as previously described (32). Polyclonal rabbit anti-B.…”
Section: Methodsmentioning
confidence: 99%